Inorganic Phosphate and Sulfate Transport in S. cerevisiae - Samyn, D R; Persson, B L (Advances in experimental medicine and biology, 2016)
Inorganic ions such as phosphate and sulfate are essential macronutrients required for a broad spectrum of cellular functions and their regulation. In a constantly fluctuating environment microorganisms have for their survival developed specific nutrient sensing and transport systems ensuring that the cellular nutrient needs are met. This chapter focuses on the S. cerevisiae plasma membrane localized transporters, of which some are strongly induced under conditions of nutrient scarcity and facilitate the active uptake of inorganic phosphate and sulfate. Recent advances in studying the properties of the high-affinity phosphate and sulfate transporters by means of site-directed mutagenesis have provided further insight into the molecular mechanisms contributing to substrate selectivity and transporter functionality of this important class of membrane transporters.